Extracorporeal Membrane Oxygenation for the Support of Adults With Acute Myocarditis. Issue 5 (May 2015) - Diddle, J. Wesley; Almodovar, Melvin C.; Rajagopal, Satish K.; Rycus, Peter T.; Thiagarajan, Ravi R.
Abstract : Objectives: To characterize survival outcomes for adult patients with acute myocarditis supported with extracorporeal membrane oxygenation and identify risk factors for in-hospital mortality. Design: Retrospective review of Extracorporeal Life Support Organization registry database. Setting: Data reported to Extracorporeal Life Support Organization by 230 extracorporeal membrane oxygenation centers. Patients: Patients 16 years old or older supported with extracorporeal membrane oxygenation for myocarditis during 1995 to 2011. Interventions: None. Measurements and Main Results: There were 150 separate runs of extracorporeal membrane oxygenation for 147 patients with a diagnosis of acute myocarditis in the Extracorporeal Life Support Organization database from 1995 through 2011. Survival to hospital discharge was 61%. Nine patients underwent heart transplantation, and transplant-free survival to discharge was 56%. Extracorporeal membrane oxygenation was deployed during extracorporeal cardiopulmonary resuscitation in 31 patients (21% of the cohort). In a multivariate model evaluating pre–extracorporeal membrane oxygenation and extracorporeal membrane oxygenation support factors, pre–extracorporeal membrane oxygenation arrest (adjusted odds ratio, 2.4; 95% CI, 1.1–5.0) and need for higher extracorporeal membrane oxygenation flows at 4 hours post–extracorporeal membrane oxygenation cannulation (odds ratio, 2.8; 95% CI, 1.1–7.3) were associated with increased odds of in-hospital mortality. In a second multivariate model evaluating adverse events while on extracorporeal membrane oxygenation, central nervous system injury (odds ratio, 26.5; 95% CI, 7.3–96.6), renal failure (odds ratio, 3.6; 95% CI, 1.4–9.3), arrhythmia (odds ratio, 5.8; 95% CI, 2.2–15.1), and hyperbilirubinemia (odds ratio, 9.1; 95% CI, 2.6–31.8) were associated with increased odds of in-hospital mortality. Conclusions: Extracorporeal membrane oxygenation can be used effectively in adults with myocarditis to support the circulation while awaiting myocardial recovery. Early extracorporeal membrane oxygenation deployment prior to cardiac arrest may be associated with better outcomes.